Time-varying spillover effect among oil price and macroeconomic variables - Worrawat Saijai (2019)
© Springer Nature Switzerland AG 2019. A purpose of this study is to examine a dynamic relationship between oil price and macroeconomic variables namely consumer price index, interest rate, effective exchange rate, and broad money (M3). The rising prices of oil could affect producer’s cost and, in turn, lead to rising average prices of all goods by theory. This situation is called inflation which can be observed from an increase in some macroeconomic indicators such as consumer price index. However, as the oil price are changing over time due to political and economic situations, the relationship between macroeconomic indicators should have more dynamic property. Therefore, this study employed the time-varying VAR model to examine this non-constant relationship. The estimated results show that the effect of oil price on some variables are time-varying while the other variable is constantly affected by the oil price.